The levels of composition in Surat Al-Kahf (like the two men as a model) (Journal of the College of Basic Education, 2023)
I seek refuge in God from the accursed Satan, in the name of God, the Compassionate, the Merciful, and praise be to God, Lord of the worlds. Abomination, and purify them with a thorough purification, and its companions, those who seek refuge in it, and those who follow its path and those who follow its straight path. As for what follows, one of the topics that my soul loves, that my tongue expresses, and my pen starts with, are the Qur’anic topics and research on them. In the subject of Quranic text analysis for students of the Department of Arabic Language - College of Education - Ibn Al-Rushd - University of Baghdad,